2005
DOI: 10.2188/jea.15.48
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitudes toward Suicide and Depression among Japanese in Municipalities with High Suicide Rates

Abstract: Questionnaire surveyA questionnaire survey was carried out from February through June in 2002. For the survey, we selected four of six municipalities in the Kuji District, and three of seven municipalities in the Miyako District, which is located south of the Kuji District. Among the seven municipalities selected for the study, three (two in Kuji and one in Miyako) are in coastal areas and four (two in Kuji and two in Miyako) are located inland. A total of 7,136 people, aged 20 to 79 years, were randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…9 The prevalence of a suicide-permissive attitude was slightly lower than in a recent study in a neighbouring area of Japan. 19 In addition, we found that poor mental health literacy was significantly associated with being male, being elderly, and having a lower level of education.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…9 The prevalence of a suicide-permissive attitude was slightly lower than in a recent study in a neighbouring area of Japan. 19 In addition, we found that poor mental health literacy was significantly associated with being male, being elderly, and having a lower level of education.…”
Section: Discussionmentioning
confidence: 73%
“…However, the level of mental health literacy in Japan had still not been sufficiently evaluated. 19,20 Therefore, we conducted a study to evaluate mental health literacy in specific rural communities. Mental health literacy was assessed based on the cognition of depression, the attitude toward depression, and the acceptance of suicide.…”
mentioning
confidence: 99%
“…Recent figures also show that more than 30,000 people commit suicide each year in Japan. Several epidemiologic studies [2][3][4][5][6][7][8] have indicated risk factors for suicide, such as depression, severe anxiety, substance abuse, poor interpersonal relationships including social isolation, inability to maintain a job, anhedonia, somatic diseases, financial problems, and personal or familial history of suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been said that knowledge of and attitudes toward suicide and depression are correlated with suicide rate [6]. It may thus be necessary to improve the mental health literacy of the target population and enable them to seek help when they most need it.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study of background factors associated with suicide in Japan, some of the possible causes behind suicide included bullying, truancy, overwork, and debts/loans, including debts due to gambling [6]. Among 33334 suicide deaths in 2010, the National Police Agency of Japan reported 22.3% were related to economic problems, with 19.6% due to debts/loans, including multiple debts.…”
Section: Introductionmentioning
confidence: 99%